2009
DOI: 10.2478/s11686-009-0045-z
|View full text |Cite
|
Sign up to set email alerts
|

The phylogeny of the Lepocreadioidea (Platyhelminthes, Digenea) inferred from nuclear and mitochondrial genes: Implications for their systematics and evolution

Abstract: The phylogenetic relationships of representative species of the superfamily Lepocreadioidea were assessed using partial lsrDNA and nad1 sequences. Forty-two members of the family Lepocreadiidae, six putative members of the Enenteridae, six gyliauchenid species and one Gorgocephalidae, were studied along with 22 species representing 8 families. The Lepocreadioidea is found to be monophyletic, except for the two species of the putative enenterid genus Cadenatella, which are found to be only distantly related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
84
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 79 publications
6
84
0
1
Order By: Relevance
“…According to Bray [17] the Lepocreadioidea include ten families, namely the Lepocreadiidae, Acanthocolpidae, Apocreadiidae, Brachycladiidae, Deropristidae, Enenteridae, Gorgocephalidae, Gyliauchenidae, Liliatrematidae and Megaperidae. Nevertheless, based on molecular analyses, Bray et al [18] and more recently Bray and Cribb [19] re-organized the superfamily Lepocreadioidea. Bray et al [18] found the Lepocreadioidea to be monophyletic and constituted by six well-supported groups, which are presently considered families according to Bray and Cribb [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Bray [17] the Lepocreadioidea include ten families, namely the Lepocreadiidae, Acanthocolpidae, Apocreadiidae, Brachycladiidae, Deropristidae, Enenteridae, Gorgocephalidae, Gyliauchenidae, Liliatrematidae and Megaperidae. Nevertheless, based on molecular analyses, Bray et al [18] and more recently Bray and Cribb [19] re-organized the superfamily Lepocreadioidea. Bray et al [18] found the Lepocreadioidea to be monophyletic and constituted by six well-supported groups, which are presently considered families according to Bray and Cribb [19].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, based on molecular analyses, Bray et al [18] and more recently Bray and Cribb [19] re-organized the superfamily Lepocreadioidea. Bray et al [18] found the Lepocreadioidea to be monophyletic and constituted by six well-supported groups, which are presently considered families according to Bray and Cribb [19]. These families are the Lepocreadiidae, the Aephnidiogenidae and the Lepidapedidae, which were previously considered by Bray [20] as three subfamilies of the Lepocreadiidae s.l., and the Enenteridae, Gorgocephalidae and Gyliauchenidae.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic DNA was isolated using the DNeasy TM Tissue Kit (Qiagen, Hilden, Germany), following manufacturer's instructions. The 28S ribosomal DNA was amplifi ed using the primers, LSU5 (F) (5′-TAGGTCGACCCGCTGAAYTTAAGCA-3′) (Bray et al, 2009) and 1500R (5′-GCTATCCTGAGGGAAACTTCG-3′) (Tkach et al, 2003) in a 25 μl reaction mixture consist of 3 μl genomic DNA, 4 μl 1 mM deoxyribonucleotide triphosphates (dNTPs, Biotools, Spain), 0.6 μl of each primer, 2.5 μl of 10x Taq buffer (Biotools, Madrid, Spain), 0.5 μl of Taq polymerase (1U; Biotools, Madrid, Spain) and 13.8 μl of distilled water. The PCR cycling profi le were performed in a Mastercycler personal-22331 (Eppendorf, Hamburg, Germany) as follows: an initial denaturation at 94 °C for 3 min, followed by 35 cycles at 94 °C for 40 s, 56 °C for 1 min, 72 °C for 1 min, completed with terminal extension at 72°C for 7 min and then stored at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In India, for platyhelminthes taxonomy morphological differences have been widely used to discriminate between species. Though, traditional diagnostic tools are now complemented by molecular techniques for resolving the taxonomic confusions coupled with species descriptions (Prasad et al, 2011;Chaudhary et al, 2015;Chaudhary et al, 2016). In India, there is a scarcity of molecular tools in studies of trematode parasites.…”
Section: Introductionmentioning
confidence: 99%
“…It is striking that, in almost every instance in which groups of trematodes are subjected to molecular phylogenetic analysis, unexpected but plausible changes in our understanding of relationships emerge (e.g. Choudhury et al, 2007;Bray et al, 2009;Cutmore et al, 2013;Pulis et al, 2014;Pinto et al, 2015). Despite this, the field can be considered to be in its infancy with the vast majority of genera and species not yet subjected to molecular phylogenetic analysis.…”
mentioning
confidence: 99%